Artificial Intelligence and Big Data Applications (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Artificial intelligence and big data applications are present in almost every corner of life. This reprint of the Special Issue entitled “Artificial Intelligence and Big Data Applications” contains a wide range of works with comprehensive information on image processing, natural language processing, computer vision, sentiment analysis, voice and gesture analysis, and other topics in the field. The latest works in multidisciplinary applications such as legal, healthcare, smart society, cyber–physical systems, and smart agriculture, among others, are also included. This compilation will spark the interest of researchers in the aforementioned fields and will serve as a knowledge base for further research in the future.